Porous gold nanomesh films electrodeposited in toluene-based dynamic soft template. (10th September 2022) - Shiba, Shunsuke; Yoshimoto, Soichiro; Hashiguchi, Shunta; Kunitake, Masashi; Kato, Dai; Niwa, Osamu; Matsuguchi, Masanobu
Abstract: Two-dimensional (2D) metallic nanomaterials have received much attention as next-generation materials. The creation of the characteristic pores into 2D metallic materials is expected to improve performance in sensing, surface-enhanced Raman spectroscopy, electrocatalytic activity, and so on. Here, we report that gold electrodeposition in a toluene-based bicontinuous microemulsion (BME), called a dynamic soft template, provides porous gold nanomesh (PGNM) film. The selective toluene adsorption onto Au{111} surfaces induces anisotropic 2D growth of gold in the aqueous phase of BME, and an intertwined network of water and toluene nanochannels in BME resulted in the formation of abundant in-plane nanopores. Toluene adsorption during Au electrodeposition makes the {111}-oriented Au surfaces more lipophilic, i.e., a structural change in BME is induced to expose the organic phase solution selectively to the toluene-adsorbed {111} Au surfaces. This dynamic change in the BME solution structure during electrodeposition might enhance the anisotropic growth of gold (dynamic soft templating). Electrochemical behaviors of low-index planes of Au electrode supported the growth mechanism of PGNM film.